Development of Leading Sectors: A Policy Recommendtion for Inclusive Economic Growth In Pangkajene Regency and the Islands - Sobirin; Juharni; Sulfianna; Irwan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The purpose of this study is to analyze how the development of leading sectors integrated with strengthening public services can encourage inclusive economic growth in Pangkajene and Kepulauan Regency. Furthermore, this study aims to provide adaptive and targeted policy recommendations to increase productivity, competitiveness, and equitable distribution of economic benefits for local communities. This study uses a descriptive qualitative method with data collection through in-depth interviews, documentation, and observation, then analyzed using Nvivo 12 Plus software to identify patterns and themes. The study's findings confirm that collaboration between the development of leading sectors—especially fisheries and agriculture—and the strengthening of responsive and integrated public services is crucial to encouraging inclusive economic growth in Pangkajene and Kepulauan Regency. The successful development of this sector depends on improving productive infrastructure and human resource capacity, as well as utilizing appropriate technology, supported by cross-regional coordination and digital transformation, to accelerate service access and reduce regional disparities. However, challenges such as limited infrastructure, human resource disparities, weak coordination, limited budgets, and low technological innovation hamper progress. Therefore, the study recommends an integrated policy that prioritizes infrastructure investment based on local potential, human resource development, innovative financing, and green and blue economy approaches to ensure sustainable growth and equitable distribution of economic benefits.